(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction: Developing countries face rapid population growth due to high fertility rates and low contraceptive prevalence. Nigeria exemplifies this challenge with a high maternal mortality rate and low contraceptive use. Unintended pregnancies, often resulting from inadequate contraceptive measures, contribute significantly to maternal and child mortality. Family planning is a critical intervention that can prevent these outcomes by enabling individuals and couples to anticipate and achieve their desired number of children, thereby improving maternal and child health. Understanding the knowledge, attitudes, and practices surrounding family planning among women of reproductive age is crucial for developing targeted interventions to enhance contraceptive uptake and overall reproductive health. Objectives: This study aims to assess the knowledge, attitudes, and practices of modern family planning among women of reproductive age in Egbeda Local Government Area, Ibadan, Oyo State. Method of Analysis: A structured questionnaire was administered to 250 women aged 18 and above using simple random sampling. Data were analyzed using SPSS version 21, employing descriptive statistics and chi-square tests for hypothesis testing, with a significance level set at P<0.05. Results: Awareness of modern family planning methods was high (100%), with primary sources being family and friends (56.2%), health workers (28.1%), and media (10.7%). Specific methods recognized included male condoms (100%), implants (96.0%), pills (90.0%), and injectable (89.9%). Benefits of family planning such as preventing unwanted pregnancies (93.2%), child spacing (96.8%), preventing sexually transmitted diseases (92.0%), improving family health (76.0%), and reducing family size (80.0%) were well understood. Perceptions of modern contraceptives were generally positive, with 86.0% considering them safe and 90.0% effective. Social acceptance varied, but most respondents (72.0%) were open to using modern contraceptives if accessible. Male involvement in family planning decisions was strongly supported (80.0%). The need for more education and awareness programs was emphasized by 80.0% of respondents. Conclusion: While awareness of modern family planning is high, actual usage lags, especially for methods like male condoms. There is a clear understanding of family planning benefits, but access issues, cultural beliefs, religious beliefs, and misinformation remain barriers. Enhancing education, improving access, and addressing cultural concerns are essential for better family planning uptake.